2006
DOI: 10.2193/0091-7648(2006)34[691:atosdm]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

A Typology of South Dakota Muzzleloader Deer Hunters

Abstract: In 1999 we surveyed 1,000 randomly selected South Dakota, USA, muzzleloader deer (Odocoileus spp.) hunters using a self‐administered mail survey to gain better understanding of equipment used, skills, success, motivations, and attitudes about technology and restrictions. This sample represented 67% of the state's muzzleloader deer‐hunter population in 1999. Nine hundred and four usable surveys were returned. We conducted a K‐means cluster analysis to determine if muzzleloader hunters could be separated (based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 6 publications
2
16
1
Order By: Relevance
“…Only 11% of resident hunters and 16% of nonresident outfitter-sponsored hunters said it was extremely important to get a trophy animal when hunting. Th ese results are consistent with the findings of others such as Boulanger et al (2006) and Gigliotti (2000), who reported in their studies that small percentages of hunters were trophy hunters.…”
Section: Discussionsupporting
confidence: 92%
“…Only 11% of resident hunters and 16% of nonresident outfitter-sponsored hunters said it was extremely important to get a trophy animal when hunting. Th ese results are consistent with the findings of others such as Boulanger et al (2006) and Gigliotti (2000), who reported in their studies that small percentages of hunters were trophy hunters.…”
Section: Discussionsupporting
confidence: 92%
“…Regarding participation rates, 30% spent time and 17% spent money on creating openings/improving habitat, while 18% spent time and 20% spent money on food plot management. The participation rate for time spent on blind construction/scouting was similar to the 53-56% participation rate in pre-season scouting activities by muzzleloader hunters in South Dakota (Boulanger et al, 2006).…”
Section: Investments In Off-season Deer Hunting Activitiessupporting
confidence: 58%
“…Satisfaction ratings for scouting, for example, are on par with some in-season activities such as shooting at turkey (Wynveen, Cavin, Wright, & Hammitt, 2005). Almost half of muzzleloader hunters spent time scouting (Boulanger, Hubbard, Jenks, & Gigliotti, 2006), and scouting has been mentioned in other research (e.g., Champ & Bishop, 1996;Daigle, Muth, Zwick, & Glass, 1998;Gratson & Whitman, 2000). As for economics, McBryde (1995) compared costs of food plots to supplemental feeding (via feeders).…”
Section: Please Scroll Down For Articlementioning
confidence: 92%
“…Recent studies from Scandinavia are a notable exception (Kanstrup et al 2016;Støen et al 2018;Stokke et al 2018 Techniques commonly used for recreational hunting are likely to impose considerably higher animal-welfare impacts than professional harvesting or culling methods. These recreational hunting techniques include archery (Nixon et al 2001), shotguns and muzzle-loading firearms (Boulanger et al 2006), pursuit with dogs (Bradshaw & Bateson 2000), knives (feral pig hunting) (Massey et al 2011), and long-range shooting (Johnston 2017). Many adverse animal-welfare events are associated with recreational hunting, notably nonfatal wounding.…”
Section: Recreational Huntingmentioning
confidence: 99%